O dyskursie epistolarnym w świetle korespondencji Wisławy Szymborskiej i Kornela Filipowicza - Wojciechowska, Anna (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2019)
The notion of epistolary discourse is understood in this paper as a communicative event reflected in the letter or other varieties of this genre in a specific sender and receiver model. The article presents some features of epistolary discourse with reference to the correspondence between Wisława Szymborska and Kornel Filipowicz. In the first part of the study, the author situates private letters in the discursive reality and introduces the participants of such kind of correspondence. Then, the interactive aspect of epistolary discourse is examined, specifically inner and outer dialogue. After that, the elements of direct dialogue are discussed, e.g. forms of address, forms of metatext and linguistic equivalents of gestures. From the data, it can be assumed that the letters in question contain the typical features of epistolary discourse. However, original and unconventional elements seem to be part of the letters as well (e.g. employing fictitious characters in the correspondence, creating collages, linguistic stylizations, etc.).